2008
DOI: 10.1115/1.3012264
|View full text |Cite
|
Sign up to set email alerts
|

Initiation and Arrest of Delayed Hydride Cracking in Zr–2.5Nb Tubes

Abstract: Using Kim’s delayed hydride cracking (DHC) model, this study reanalyzes the critical temperatures for DHC initiation and arrest in Zr–2.5Nb tubes that had previously been investigated with the previous DHC models. At the test temperatures above 180°C, DHC initiation temperatures fell near the terminal solid solubility for precipitation temperatures, requiring some undercooling or ΔT from the terminal solid solubility for dissolution (TSSD) temperatures, and increased toward TSSD with the number of thermal cycl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2009
2009
2010
2010

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(17 citation statements)
references
References 18 publications
0
17
0
Order By: Relevance
“…A simple calculation assuming the growth of a crack to be 0.9 times the thickness over 2 years shows that the crack growth rate was at the least 5.9 9 10 À12 m/s, [25] which is over 10 4 times faster than the predicted crack growth rate, 1.6 9 10 À16 m/s, [7] by the old DHC models. In contrast, Kim [25] has shown that DHC at low temperatures below 180°C occurs due to stress-induced hydride phase transformation from c to d at a crack tip, creating a difference in hydrogen concentration between the bulk and a crack tip due to a higher hydrogen solubility of the c-hydride, which is a driving force for DHC, using Kim's DHC model [5,14,18,20,21] and the experimental facts [26][27][28][29] reported, as shown in Figure 11. Given that the c-hydride is formed at low temperatures below 180°C for the slow-cooled zirconium alloys [30] such as spent fuel rods, it is not until the spent fuel rods are cooled to below 180°C that DHC occurs due to stress-induced hydride phase transformation from c to d. According to Einziger's model, [31] it is predicted to take at least 30 years for cladding temperature to completely fall to below 180°C, as shown in Figure 12.…”
Section: B Dhc Of the Spent Fuel Rodsmentioning
confidence: 96%
See 4 more Smart Citations
“…A simple calculation assuming the growth of a crack to be 0.9 times the thickness over 2 years shows that the crack growth rate was at the least 5.9 9 10 À12 m/s, [25] which is over 10 4 times faster than the predicted crack growth rate, 1.6 9 10 À16 m/s, [7] by the old DHC models. In contrast, Kim [25] has shown that DHC at low temperatures below 180°C occurs due to stress-induced hydride phase transformation from c to d at a crack tip, creating a difference in hydrogen concentration between the bulk and a crack tip due to a higher hydrogen solubility of the c-hydride, which is a driving force for DHC, using Kim's DHC model [5,14,18,20,21] and the experimental facts [26][27][28][29] reported, as shown in Figure 11. Given that the c-hydride is formed at low temperatures below 180°C for the slow-cooled zirconium alloys [30] such as spent fuel rods, it is not until the spent fuel rods are cooled to below 180°C that DHC occurs due to stress-induced hydride phase transformation from c to d. According to Einziger's model, [31] it is predicted to take at least 30 years for cladding temperature to completely fall to below 180°C, as shown in Figure 12.…”
Section: B Dhc Of the Spent Fuel Rodsmentioning
confidence: 96%
“…Figure 8 shows the DHC initiation temperatures with hydrogen concentration of the Zr-2.5Nb specimens that have been determined only after the first thermal cycle. [18] Under stresses, DHC initiation occurred at the TSSP2 or higher temperatures, not at the TSSP1 temperatures. Given the results of Figure 8, nucleation of hydrides that is the first step of DHC must have occurred at higher temperatures prior to reaching the DHC initiation temperatures due to stresses.…”
Section: A Creep Effect On Hydride Reorientationmentioning
confidence: 98%
See 3 more Smart Citations